High Strain Rate Behavior of a Sic Particulate Reinforced Al2o3 Ceramic Matrix Composite - Hall, Ian W.; Güden, Mustafa; Güden, Mustafa (Elsevier Ltd., 1998)
The high strain rate deformation behavior of composite materials is important for several reasons. First, knowledge of the mechanical properties of composites at high strain rates is needed for designing with these materials in applications where sudden changes in loading rates are likely to occur. Second, knowledge of both the dynamic and quasi-static mechanical responses can be used to establish the constitutive equations which are necessary to increase the confidence limits of these materials, particularly if they are to be used in critical structural applications. Moreover, dynamic studies and the knowledge gained form them are essential for the further development of new material systems for impact applications. In this study, the high strain rate compressive deformation behavior of a ceramic matrix composite (CMC) consisting of SiC particles and an Al{sub 2}O{sub 3} matrix was studied and compared with its quasi-static behavior. Microscopic observations were conducted to investigate the deformation and fracture mechanism of the composite.
Keywords: High strain rate; Composite materials; Ceramic materials; Reinforced materials